Analysis of the Quality of the e-Raport Information System at SMPN 5 Tangerang City on User Satisfaction Using the WebQual 4.0 Method. - Monalisa Monalisa; Imron Imron; Albert Riyandi (INFOTECH journal, 2021)
The e-Raport system is used as an information system designed by schools to inform parents of student development by schools, which has been implemented in all state schools in various provinces in Indonesia including Banten province. SMPN 5 Tangerang is one of the public schools in Tangerang city that uses the e-Raport System as a substitute for reports of students' learning outcomes manually. The problem raised in this study is whether the quality of the e-Raport System affects user satisfaction. This research focuses on user satisfaction e-Raport system using webQual 4.0 method consisting of 3 variables namely usability, information quality, and interaction quality. The data used in the primary data, namely by distributing questionnaires using a likert scale with 20 points of statement to 400 respondents. Data obtained and processed using multiple linear regression analysis techniques using SPSS software. Based on webqual variable 4.0, the analysis results showed that the quality of usefulness, information quality, and interaction quality influenced user satisfaction.